A new spider mite species of Schizotetranychus (Acari: Prostigmata: Tetranychidae) from Quercus gilva in Japan - Ehara, Shôzô; Ohashi, Kazunori (Zootaxa, 2005)
A new spider mite, Schizotetranychus gilvus sp. nov. (Acari: Prostigmata: Tetranychidae), is described and illustrated from specimens collected on an evergreen oak, Quercus gilva (Fagaceae), in Kyoto (type locality) and Nara, Honshu, Japan.